Differences in Leukocyte (White Blood Cell) Levels and Their Potential as a Predictor of Preeclampsia in Pregnant Women - Karmila, Hartatiek Nila; Nathalya Dwi Kartika Sari; Ika Mardiyanti; Nur Sophia Matin (Jurnal Penelitian Keperawatan Kontemporer, 2026)
Background: Preeclampsia is a pregnancy complication that significantly contributes to maternal and perinatal morbidity and mortality. Systemic inflammation plays a key role in its pathogenesis, and leukocytes (white blood cells/WBC) are potential biomarkers associated with this condition. Objective: This study aimed to analyze differences in leukocyte levels between normotensive and preeclamptic pregnant women and to evaluate their potential as predictors of preeclampsia. Methods: This was an observational analytic study with a cross-sectional design involving 62 pregnant women, consisting of 33 normotensive and 29 preeclamptic subjects. Leukocyte levels were obtained from laboratory examinations. Differences were analyzed using the independent t-test, while predictive ability was assessed using Receiver Operating Characteristic (ROC) analysis and Area Under the Curve (AUC). Results: The mean leukocyte level in the normotensive group was 9.79 ± 2.32 ×10³/µL, while in the preeclampsia group it was 10.45 ± 3.20 ×10³/µL. There was no statistically significant difference between the two groups (p = 0.363). ROC analysis showed an AUC value of 0.56, indicating weak predictive ability. Conclusion: Leukocyte levels tend to be higher in preeclamptic pregnant women; however, the difference is not statistically significant and shows poor predictive performance. Therefore, WBC cannot be used as a single predictor of preeclampsia.